Impact of Age Initiation and Duration of Hemodialysis on Impaired Cognitive Function Experienced by Chronic Kidney Disease (CKD) Patients - Rini Nindela; Sigit Nur Prastowo; Eka Febri Zulissetiana; Selly Marisdina; Siti Sarahdeaz Fazzaura Putri (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
The prevalence of people with chronic kidney disease (CKD) in Indonesia increases with age. Various complications to death can occur in CKD patients, one of which is impaired cognitive function. In addition, end-stage CKD treatment options, such as hemodialysis, further increase the risk of complications of cognitive impairment in CKD patients. About 10%-40% of CKD patients experience a decline in cognitive function. This study aims to determine the factors that influence the occurrence of cognitive impairment in hemodialysis patients. This study was conducted at Mohammad Hoesin Hospital Palembang in October-November 2022. Cognitive decline was detected by examination of the Montreal Cognitive Assessment-Indonesian version (MoCA-Ina) while other variables were obtained through interviews. The data were analyzed with Chi-square or Fisher exact tests. Age, education level, and age at hemodialysis initiation affect global cognitive function in CKD patients. In cognitive domain analysis, a significant relationship was found between age and duration of hemodialysis and attentional function, as well as the impact of age, sex, and age at hemodialysis initiation on executive/visuospatial function. Several demographic and hemodialysis characteristics are associated with cognitive decline in hemodialysis patients. Education and periodic cognitive screening are necessary to prevent and detect cognitive decline in these at-risk populations.